Covalent Organic Framework Derived Boron/Oxygen Codoped Porous Carbon on CNTs as an Efficient Sulfur Host for Lithium–Sulfur Batteries. Issue 11 (26th June 2019) - Chen, Xiudong; Xu, Yanjun; Du, Fei‐Hu; Wang, Yong
Abstract: Boron/oxygen co‐doped carbons (BOC) have great potentials as sulfur host materials for lithium–sulfur batteries, because they can increase electronic conductivity and anchor polysulfides. However, the doping interface as a key chemically active site still lacks in‐depth understanding owing to the difficulty in design at the molecular scale. Herein, the BOC network derived from covalent organic framework (COF) is prepared on the surface of CNTs via rational design of the organic condensation reaction. This strategy enables boron and oxygen heteroatoms to be uniformly doped throughout porous carbon because of the uniformly‐distributed two elements in the COF precursor. Thereby, the BOC matrix is demonstrated to play a pivotal role in promoting the chemical absorption of polysulfides and enhancing cycling stability. The BOC@CNT with 68.5% sulfur shows superior lithium polysulfides absorptivity and displays superior electrochemical performances as a cathode for Li–S batteries, including a large reversible capacity (1077 mA h g −1 after 200 cycles at 0.2 C), and outstanding cycling stability (794 mA h g −1 after 500 cycles at 1 C). The demonstrated strategy for fabricating BOC network by COF precursor for Li–S batteries provides a new approach to rationally design uniform heteroatom interfaces for good electrochemical performances. Abstract : The covalent organic framework (COF‐10) is in situ prepared on the exterior surface of carbon nanotubes (CNTs) and then converted to boron/oxygen codoped porous carbon (BOC) for Li–S batteries. The BOC@CNT/S cathode can deliver highly reversible large capacities of 1077 mA h g −1 after 200 cycles at 0.2 C and 794 mA h g −1 at 1 C after 500 cycles.